The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/epigenomes4030013
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color in Apple Fruit (Malus × domestica): Genetic and Epigenetic Insights

Abstract: Apple skin color is an important trait for organoleptic quality. In fact, it has a major influence on consumer choice. Skin color is, thus, one of the most important criteria taken into account by breeders. For apples, most novel varieties are so-called “mutants” or “sports” that have been identified in clonal populations. Indeed, many “sports” exist that show distinct phenotypic differences compared to the varieties from which they originated. These differences affect a limited number of traits of economic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
0
5
0
1
Order By: Relevance
“…Color is a crucial quality parameter for apples that is used to determine the fruit's maturity and ripeness [222][223][224]. The skin color of an apple is influenced by various factors, including genetics, environmental conditions, and postharvest handling [225][226][227]. The geographical locations of orchards can influence the color of apples as well [228].…”
Section: Colormentioning
confidence: 99%
“…Color is a crucial quality parameter for apples that is used to determine the fruit's maturity and ripeness [222][223][224]. The skin color of an apple is influenced by various factors, including genetics, environmental conditions, and postharvest handling [225][226][227]. The geographical locations of orchards can influence the color of apples as well [228].…”
Section: Colormentioning
confidence: 99%
“…DNA methylation, which is one of an epigenetic modification, has been suggested that was involved in the fruit color of woody plants, but the mechanism that mediates DNA methylation is not fully understood [ 37 ]. In this study, the ‘Fuji’ cultivar retaining red-striped skin on its fruit turned red-blushed skin with the upregulation of MdMYB10 expression when the paper-bag was removed.…”
Section: Discussionmentioning
confidence: 99%
“…The dark red color of apples is determined by the ratio of the quantitative composition of anthocyanins to chlorophyll. Apples with a higher content of chlorophyll than anthocyanins in the skin have a dark red color, while a light red color of the apple skin means that the content of anthocyanins is higher than that of chlorophyll [30]. In a study conducted in 2008, Iglesias et al found that anthocyanin content strongly correlated with red (a*) and yellow (b*) co-ordinate values [5].…”
Section: Changes Inmentioning
confidence: 99%
“…Color and size are important quality parameters that determine the market value of apples, as well as the consumers' choice [3,29]. Anthocyanins are biologically active compounds that determine the pink hues of the apples and their commercial appearance and primary choice [5,30]. Guan et al pointed out that the repetitive purchase and consumption of fruit depends on their taste, aroma, and texture [31].…”
Section: Introductionmentioning
confidence: 99%